Mobile applications as intervention tools for children with ADHD for a sustainable education. - Doulou, Aikaterini; Drigas, Athanasios; Skianis, Charalampos (Technium Sustainability, 2022)
Mobile applications are constantly increasing and people are trying to find solutions to problems in their daily life in the digital world. Digital developments provide equal access and learning opportunities to people with disabilities. Today, children spend most of their time using mobile devices. Therefore, addressing their difficulties through mobile applications would be very effective. E-learning applications that use mobile devices, also known as mobile learning, can be used as therapeutic tools to improve both executive functions and quality of life. Moreover, they create greater motivation in children and adolescents by increasing the frequency of practicing cognitive and metacognitive task skills. In addition, audiovisual stimuli provided through smartphone applications can facilitate the understanding and memorization of the information provided. Therefore, they can be essential learning tools for children with ADHD. The present work investigates the role and effectiveness of using mobile applications in order to improve the quality of life of children with ADHD.